Co-movement of Indonesian state-owned enterprise stocks - Apriani Dorkas Rambu Atahau; Robiyanto Robiyanto; Andrian Dolfriandra Huruta (Economies, 2023)
According to portfolio theory, diversifying investment to several stocks with negative correlations may reduce portfolio risk. In contrast, combining stocks with similar movement (co-movement) has no impact on portfolio risk reduction. This study aims to examine state-owned enterprise stock co-movement in Indonesia using orthogonal generalized auto-regressive conditional heteroscedasticity (O-GARCH) to help investors selectively choose stocks in a portfolio to reduce portfolio risks. Saturation sampling was used since all state-owned enterprise stocks listed on the Indonesian Stock Exchange were selected as samples. Based on monthly data from January 2013 to December 2021, the O-GARCH method was able to simplify the covariance matrix of the 17 SOEs. Of 17 SOEs, 11 had co-movement, as indicated by their similar principal components, whereas the remaining 6 stocks had a different principal component. Hence, investment managers or investors should not put the eleven stocks in the same portfolio as they have similar risk factors; instead, they may combine them with the six remaining SOE stocks which have a different co-movement. In addition, when the fiscal deficit is high and unconventional monetary policy is implemented in a crisis period, the SOE stock co-movement is higher. Thus, the SOE stock co-movement also depends on government-related matters and faces slightly different risks compared to its private-sector counterparts. Hence, the regulators formulating the policy on SOE stock holdings may use the results of this study by considering the potential merging of the SOE stocks with a similar stock return co-movement by taking account the timing in relation to fiscal deficit and crisis period.
Keywords: 330; orthogonal GARCH; principal component analysis; state-owned enterprises; stock returns